Analisis Pengaruh Implementasi Web Sebagai Media Promosi Terhadap Pertambahan Anggota Komunitas SKSP - Dias Ayu Budi Utami; Sarmini -; Melyana Fatmah Kartikasari (Jurnal SIFO Mikroskil, 2018)
The development of information increasingly strict follow the development of the era. The sooner the information the performance of a company and agencies considered to have a good performance in the eyes of the client and the community. Especially educational institutions ie colleges are increasingly growing especially in the academic system. These developments have an impact on the speed of information from the institution to the students and the outside community, especially the guardian of the students. For example from the student affair held a dies natalis event by making the booth and then invite the community around and guardian pupils. Information will quickly spread if using online media. Online-based information system used in this study is using the web.In addition, accelerate information from universities to students and other benefits society is as a medium of college promotion by creating a web profile college that can be accessed anytime and anywhere. Seeing from these benefits the community makes online media used to promote their communities. One community that is in college STMIK AMIKOM Purwokerto is School of Writing Letters Amikom Purwokerto. To increase the number of members, the community requires online promotional media. From the results of this study can be concluded that the promotion through the web can increase the number of members of the community SKSP (School of Writing Letters Amikom Purwokerto)